N‐acetylcysteine reduces cocaine‐seeking behavior and anterior cingulate glutamate/glutamine levels among cocaine‐dependent individuals - Woodcock, Eric A.; Lundahl, Leslie H.; Khatib, Dalal; Stanley, Jeffrey A.; Greenwald, Mark K. (Addiction biology, 2021)
N‐acetylcysteine (NAC) is a cystine prodrug shown to reduce cocaine‐ and cue‐primed reinstatement of cocaine‐seeking behavior in preclinical studies. In this inpatient study, the effects of NAC maintenance versus placebo on cocaine‐seeking behavior were examined during cocaine‐primed and unprimed self‐administration sessions among non‐treatment‐seeking, cocaine‐dependent individuals. Twelve participants completed this double‐blind, placebo‐controlled, within‐subject crossover study. Each participant was maintained for 1 week (Sat–Fri) on NAC (1200‐mg TID; 3600 mg/day total) and 1 week on placebo (0‐mg TID); medication order was randomized. A subset of participants underwent proton magnetic resonance spectroscopy scans (n = 8) on the third day of medication (Mon) to assess neurochemistry in the rostral anterior cingulate (rACC; voxel = 4.5 cm3). In four randomized sessions (Tue–Fri) each week, each participant could earn unit amounts of cocaine (10 mg, fixed) versus money ($0.50 vs. $1.50) on a choice, progressive ratio schedule after insufflating active versus placebo cocaine‐priming doses (110 mg vs. 4 mg). Relative to the placebo priming dose, the active cocaine priming dose (110 mg) increased cocaine‐seeking behavior (p = .003). NAC reduced cocaine‐primed cocaine‐seeking behavior compared with placebo levels (p = .044) but did not alter placebo‐primed cocaine‐seeking behavior. The larger money alternative ($1.50) suppressed cocaine‐seeking behavior relative to the smaller money alternative ($0.50; p = .011). Compared with placebo levels, NAC significantly decreased rACC glutamate + glutamine levels (p = .035) and numerically decreased rACC glutamate levels (p = .085). These preliminary findings indicate that NAC suppresses cocaine‐seeking behavior in some, but not all, experimental scenarios. Further, our findings suggest NAC may exert its therapeutic effects by modulating excitatory tone in the rACC. In this double‐blind, placebo‐controlled, and within‐subject crossover study, cocaine‐priming significantly increased cocaine‐seeking behavior among cocaine dependent individuals during a continuous 16‐day inpatient stay. N‐acetylcysteine (NAC) maintenance dosing (3600 mg/day; PO) significantly attenuated cocaine‐primed cocaine‐seeking behavior and significantly decreased rostral anterior cingulate cortex (rACC) glutamate + glutamine levels. Finally, a higher money alternative amount ($1.50 vs. $0.50) suppressed cocaine‐seeking behavior, analogous to continency management, but did not exhibit additive effects when combined with NAC dosing in our human laboratory paradigm.